Peran Manajemen Konflik terhadap Performansi Kerja dan Produktivitas Organisasi pada Dinas Pariwisata dan Kebudayaan Provinsi Jawa Barat - Granit Agustina; Feby Febrian (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
West Java Province has the potential for good community economic growth through the empowerment of its government and private organizations. This empowerment is carried out because every organization often experiences obstacles and challenges related to performance and productivity conflicts in carrying out their activities. This research aims to determine the role of conflict management, work performance, and organizational productivity in the Department of Tourism and Culture of West Java. The research method used quantitative and Path analysis. Sampling was done by purposive sampling technique on the Department of Tourism and Culture of West Java Province employees, amounting to 67 of a population of 200 people. The study's results indicate that conflict influences work performance and productivity in the organization. Partially, organizational productivity dominated over work performance. Conflict often weakened a person's performance and reduced organizational productivity so that it might be appropriately handled.